2022
DOI: 10.1007/s12210-022-01064-x
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity evaluation of environmentally friendly synthesis Copper/Zinc bimetallic nanoparticles on MCF-7 cancer cells

Abstract: Bimetallic nanoparticles offer unique chemical, physical and optical properties that are not available for monometallic nanoparticles. Bimetallic nanoparticles play a major role in various therapeutic, industrial and energy fields. Recently, nanoparticles of Copper/Zinc bimetallic nanoparticles have attracted attention in various fields, especially medicine. In this study, bimetallic CuO/ZnO nanostructures were biosynthesized using plant extracts. The plant-mediated synthesis nanoparticles were characterized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 55 publications
2
27
0
Order By: Relevance
“…Phyto pathogens ground an excessive reduction in crop yields. Fungicide might be the solution for these, but over time, problems of resistance occur 78 81 . Nanoparticles have just the focus of attention with their special antimicrobial effects.…”
Section: Resultsmentioning
confidence: 99%
“…Phyto pathogens ground an excessive reduction in crop yields. Fungicide might be the solution for these, but over time, problems of resistance occur 78 81 . Nanoparticles have just the focus of attention with their special antimicrobial effects.…”
Section: Resultsmentioning
confidence: 99%
“…This differs from a result of a study from Saudi Arabia where the main percentage was the chest and abdomen. 26,27 This may be explained by the fact that the cautery site was usually on the site of symptoms, which were mostly diarrhea and vomiting in our study, whereas abdominal distension and prolonged cough in another study.…”
Section: Discussionmentioning
confidence: 58%
“…Some researchers have shown that the toxicity of carbon nanomaterials to the cell is usually induced by the oxidative stress that arises either through the generation of reactive oxygen species (ROS), where it has been observed that the production of reactive oxygen species is directly related to the concentration of graphene oxide and the exposure time, or it may produce oxidative stress in a non-dependent manner. ROS where nanomaterials damage or oxidize certain components in the cell and this leads to oxidative stress (Liu et al, 2011;Zadeh et al,2022), and another study reported that the accumulation of excessive reactive oxygen species leads to lipid oxidation, lysosome membrane damage and DNA damage (Zhao et al, 2021;Ansari et al,2022).…”
Section: Discussing the Results Of The Meta-studymentioning
confidence: 99%